Linear reservoir-based adaptive land subsidence model: Case of Sumatra peat lowland forests - Nurhamidah .; A. Junaidi (International Association of Lowland Technology, 2016)
Any model of flood hazard assessment must account for the dynamic nature of floodplains related to the current states of topography. This article proposes a model of the spatialtemporal variability of land subsidence for predicting the land subsidence prone areas based on the concept of linear reservoir. The model is formulated based on analysis on data gathered from Hobo loggers plated along Sumatra deltas. It includes the soil characteristics, the differences in soil temperatures and the change of the groundwater level to factors that cause the land subsidence and effects of the subsidence on the floodplain facies. The validation of this model showed that the spatial-temporal variability of future land subsidence could be quantified, the future inundation depth of floodplains could be predicted, and the model could be applied on any peat land area with potential land subsidence problem.